Analysis of Price and Product on the Purchase Behavior of Bekasi Batik Consumers Mediated by Purchase Intention - Rastansya Anandhika; Wahyudi David (Jurnal Multidisiplin Sahombu, 2025)
Bekasi Batik, as a local product, has the potential to grow, but still faces challenges in attracting consumer interest and purchase behavior. This study aims to examine the direct effects of price and product on purchase intention and purchase behavior, as well as their indirect effects on purchase behavior through purchase intention. This research uses a quantitative approach with data collected from 96 Batik Bekasi consumers through a Google Form. Respondents consisted of consumers who made purchases directly at the Kombas workshop (East Bekasi/Blueplaza) and those who purchased online, with data analyzed using SmartPLS 3.2.9. The results show that price and product significantly influence purchase intention, but only product has a direct effect on purchase behavior, while price does not. Purchase intention acts as a significant mediator in strengthening the influence of price and product on consumer purchase behavior toward Batik Bekasi.